Haematological Parameters Alternations Resulted by Exposing Albino Mice to Shisha Smoke - F. Al-Easawi, Nada A.; N. A.Al-Azzawi, Muhammad; H. Afaj, Adnan (Iraqi Journal of Science, 2023)
In this study, effects of shisha smoking on some blood components were evaluated in (120) male adult mice. The animals were divided into four groups according to smoke types (cigarette, shisha, cigarette +shisha) in addition to control groups which exposed to fresh air only. A special inhalation chamber designed locally has been used to expose the animals. Exposed to cigarette smoke was done for 5 min/day while exposed to shisha smoke for 15 min /day /7days/weeks for 4,8,12 weeks. Blood samples were collected to evaluate some hematological variables. The results showed that RBC, WBC count, Hb, PCV, differential leukocyte (Lymphocyte, Monocyte, Neutrphils) were significantly high (P≤0.001) in groups which exposed to shisha smoke as compared with those exposed to cigarette smoke. These values were increased with increasing of exposure periods and become clearer in groups exposed for 12 weeks. It was concluded that shisha smoke contains high concentrations of toxicants as compared to cigarette smoke, and cause clear increase in some blood parameters that may led to cardiovascular disease.